Réponses

2013-12-03T14:34:23+01:00
 A = a +bc
A = 1/4 +(-3/2 * 1/3)
A = 1/4 + (-3*1)/(2*3)
A = 1/4 -3/6
On met au dénominateur commun 12
A = (3*1)/(3*4) +(2*-3)/(2*6)
A = 3/12 -6/12
A = (3-6)/12
A = -3/12
A = -(1*3)/(4*3)
A = -1/4

B = a + (b/c)
B = 1/4 +(-3/2)/(1/3) or (-3/2) / (1/3) = -3/2 * 3/1
B = 1/4 +( -3/2 * 3/1)
B = 1/4 + (-3*3)/(2*1)
B = 1/4 -9/2
On met au dénominateur commun 4
B = 1/4 - (2*9)/2*2)
B = 1/4 - 18/4
B = (1-18)/4
B = -17/4

C = a/(b+c)
C = 1/4 /(-3/2+1/3)
C = 1/4 / (-(3*3)/(2*3) + (2*1)/(2*3))
C = 1/4 / (-9/6 + 2/6)
C = 1/4 / ((-9+2)/6)
C = 1/4 / -7/6
C = 1/4 * 6/-7
C = (1*6) /(4*-7)
C = 6/-28
C =  - 6/28
C = - (2*3) / (2*14)
C = -2/2 * 3/14
C = -3/14